The Role of Islamic Boarding Schools in Preserving the Ahlusunnah Wal Jamaah Tradition in Society - Carmidin, Carmidin (CV. Tripe Konsultan, 2024)
Islamic boarding schools are one part of the various forms and types of educational institutions in Indonesia and there are so many of them. This research aims to examine the role of Islamic boarding schools in preserving the traditions of Ahlusunnah wal Jamaah in society. This research uses a library study approach by collecting data in the field or from eyewitnesses to events. The research results show that the religious traditions of Ahlusunnah wal Jama'ah that are commonly practiced in society include: Yasinan, Tahlilan, Maulid Nabi, Manaqiban, Istigosan (Tawasul). The steps taken by Islamic boarding schools to preserve these activities are: (1) Yasinan is carried out every Friday with the community in turns from house to house, (2) The Prophet's birthday is carried out by community Islamic boarding schools together by reading al barzanji simtu dhuror with hope. received the Prophet's intercession, (3) Manaqib activities are carried out by the Islamic boarding school together with each community once a week at the mosque or prayer room in the hope of seeking blessings and good role models from the ulama. previously, (4) The tradition of tawasul is still maintained by Islamic boarding schools together with the community, this activity is usually known as istigotsah, to get closer to Allah SWT through prayer, good deeds and pious people such as: prophets, friends, and guardians of Allah.